Association between Beliefs about Medication and Medication Adherence among Patients with Chronic Diseases: A Cross-Sectional Study in Sana'a, Yemen, 2025-2026 - Al-Nono, Samah Monther; Alnagmy, Dina Ezzaldin; Al-Bajli, Eshtyauq Abdo; Aldobai, Ayat Hani; Alobaidi, Lamess Abdo Algalele (My University, 2026)
Background: In conflict-affected and resource-limited settings like Yemen, maintaining medication adherence for chronic diseases is a profound clinical challenge. Objective: This study aimed to evaluate the levels of medication adherence and explore the influence of patients' beliefs about medicines among individuals with chronic conditions in Sana'a, Yemen, in 2026.